Multi-shell Polyhedral Clusters - Diudea, Mircea Vasile (Carbon Materials: Chemistry and Physics, 2018)
This volume presents new methodologies and rationalizes existing methods that are used in the design of multi-shell polyhedral clusters. The author describes how the methods used are extended from 2D-operations on maps to 3D (and higher dimensional) Euclidean space. A variety of structures is designed and described in detail and classified giving rise to an atlas of multi-shell nanostructures. The book therefore sheds a new light on the field of crystal and quasicrystal structures, an important part of nanoscience and nanotechnology. The author goes on to show how the recently established methods are used for building complex multi-shell nanostructures and how this completes the existing information in the field. The atlas of such structures is completed with atomic coordinates (included as supplementary material). The content of this book gives a useful insight into structure elucidation and suggests new material synthesis.